Analisis Pembelajaran Berbantuan Media Audio Visual Upin Ipin Episode Sholawat Allahul Kaffi Terhadap Pembentukan Karakter Religius Siswa Sekola Dasar - Jaka Nugraha; Prasnanda Bunga Rafiza (el-Ibtidaiy:Journal of Primary Education, 2022)
This study aims to analyze and describe learning aided by audio-visual media upin ipin episodes of sholawat allahul kaffi to the formation of religious character of elementary school students. The type of research used in this study was qualitative research with descriptive research methods. The data in the study were obtained through interviews, observation and documentation. Based on the results of the analysis, the effects of the Upin and Ipin films that were carried out at SDN Cicalengka X contained three processes, namely seeing/observing, applying and analyzing, which were carried out with the Upin and Ipin film media episodes of sholawat allahul kaffi. There are good religious character values for the development of children's character, namely having good morals, loving others, parents and teachers and knowing which behavior is good and which is not good at elementary school age in the surrounding environment. It can be concluded that the overall results of the analysis of the influence of the Upin and Ipin films which include the values of religious characters, namely the cultivation of good morals in children's daily lives then character values as well as the results of interviews and observations with students, teachers, parents, can be used as examples for students. in improving the character of rekigus in their social life. Based on the results of this study, the suggestion that can be conveyed is that Upin and Ipin films can be used as learning media in instilling religious character values for students. Keywords: Audio visual learning, Upin ipin film, religious character